METHODICALS FOR IMPROVING THE PROCESS OF TEACHING FUTURE ENGLISH TEACHERS TO READ ORIGINAL ARTISTIC TEXTS - Mirzayeva Zilola Makhammadjon qizi (Web of Journals Publishing, 2025)
This article explores the pedagogical processes involved in training future English language teachers to engage with authentic literary texts, drawing on empirical studies and theoretical frameworks. It examines teacher perceptions, student engagement, methodological approaches, and implications for teacher education programs. By synthesizing findings from PhD-level research, the article highlights the benefits of literature in developing language proficiency, empathy, and critical thinking, while addressing challenges such as text selection and motivation. Recommendations emphasize student-centered models and professional development to bridge theory-practice gaps in English as a Foreign Language (EFL) and English as a Second Language (ESL) contexts.
Keywords: Pre-service teachers, authentic literature, teacher education, literary competence, reading strategies, English language teaching (ELT).